Optimalisasi Desain Sistem Photovoltaic untuk Elektrifikasi Sumur Minyak Terpencil Menggunakan PVsyst - Muhtadi, M Zaky Zaim; Naufal, Muhammad Mirza; Pujianto, Pujianto; Hamdani, Chalidia Nurin (Politeknik Negeri Malang, 2025)
Sustainable power management in remote oilfield operations faces significant challenges due to grid dependency. This study evaluates a photovoltaic microgeneration system implementation at PT XYZ's oilfield facility using PVsyst simulation software. The methodology incorporates site-specific parameters to optimize system configuration for grid integration. Results show that a 4-unit monocrystalline photovoltaic array, receiving annual Global Horizon irradiation of 2008.9 kWh/m² and Global effective irradiation of 1893.9 kWh/m², achieves 2446.3 kWh/year generation capacity with 1974.6 kWh/year available for consumption. This microgeneration system meets 53.3% of the facility's 3706.9 kWh annual demand, with a Performance Ratio of 0.619, demonstrating significant potential for remote oilfield applications. The system's performance indicates opportunities for enhancement through capacity expansion, smart grid integration, and implementation of advanced monitoring systems, offering a scalable model for similar remote facilities in the oil and gas sector.